Characteristics of large‐scale nanohole arrays for thin‐silicon photovoltaics. (1st October 2012) - Chen, Ting‐Gang; Yu, Peichen; Chen, Shih‐Wei; Chang, Feng‐Yu; Huang, Bo‐Yu; Cheng, Yu‐Chih; Hsiao, Jui‐Chung; Li, Chi‐Kang; Wu, Yuh‐Renn
ABSTRACT Nanostructured crystalline silicon is promising for thin‐silicon photovoltaic devices because of reduced material usage and wafer quality constraint. This paper presents the optical and photovoltaic characteristics of silicon nanohole (SiNH) arrays fabricated using polystyrene nanosphere lithography and reactive‐ion etching (RIE) techniques for large‐area processes. A post‐RIE damage removal etching is subsequently introduced to mitigate the surface recombination issues and also suppress the surface reflection due to modifications in the nanohole sidewall profile, resulting in a 19% increase in the power conversion efficiency. We show that the damage removal etching treatment can effectively recover the carrier lifetime and dark current–voltage characteristics of SiNH solar cells to resemble the planar counterpart without RIE damages. Furthermore, the reflectance spectra exhibit broadband and omnidirectional anti‐reflective properties, where an AM1.5 G spectrum‐weighted reflectance achieves 4.7% for SiNH arrays. Finally, a three‐dimensional optical modeling has also been established to investigate the dimension and wafer thickness dependence of light absorption. We conclude that the SiNH arrays reveal great potential for efficient light harvesting in thin‐silicon photovoltaics with a 95% material reduction compared to a typical cell thickness of 200 µm. Copyright © 2012 John Wiley & Sons, Ltd.